2006
DOI: 10.1128/mcb.00315-06
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the Molecular Basis of the Interaction between NDPK-A and AMPK α1

Abstract: Nucleoside diphosphate kinase (NDPK) (nm23/awd) belongs to a multifunctional family of highly conserved proteins (ϳ16 to 20 kDa) including two well-characterized isoforms (NDPK-A and -B). NDPK catalyzes the conversion of nucleoside diphosphates to nucleoside triphosphates, regulates a diverse array of cellular events, and can act as a protein histidine kinase. AMP-activated protein kinase (AMPK) is a heterotrimeric protein complex that responds to the cellular energy status by switching off ATP-consuming pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…array approach that has recently been validated empirically. 19,24 We found that both M-LDH and H-LDH exhibit the same in vitro binding capabilities, binding the AMPK α1, AMPK β1, AMPK β2, AMPK γ1 and AMPK γ2 directly, but not the AMPK α2 isoforms of AMPK, an observation also made in the in vivo precipitation in Figure 1(b). Interestingly, our results also show that both LDH isoforms are equally capable of binding CK2β, NDPK-A and NDPK-B, but not CK2α.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…array approach that has recently been validated empirically. 19,24 We found that both M-LDH and H-LDH exhibit the same in vitro binding capabilities, binding the AMPK α1, AMPK β1, AMPK β2, AMPK γ1 and AMPK γ2 directly, but not the AMPK α2 isoforms of AMPK, an observation also made in the in vivo precipitation in Figure 1(b). Interestingly, our results also show that both LDH isoforms are equally capable of binding CK2β, NDPK-A and NDPK-B, but not CK2α.…”
Section: Discussionsupporting
confidence: 52%
“…19,24 The four peptides (NDPKpep 1, 2, 3 and 4) correspond to exposed regions of NDPK-A (amino acid residues 49-62, 92-105, 111-125 and 139-152, respectively), as determined by crystal structure with peptide 3 forming the interaction/binding region of NDPK-A for both AMPK α1 and CK2α. Figure 3(b) shows that M-LDH and H-LDH exhibit the same binding capabilities, interacting directly with/binding the AMPK α1, AMPK β1, AMPK β2, AMPK γ1 and AMPK γ2, but not the AMPK α2 isoform, similar to our finding shown in Figure 1(b), where LDH does not interact with AMPK α2 in vivo.…”
Section: Further Verification Of the Association Of Ldh With The Subsmentioning
confidence: 99%
“…The CF antigen, which is overexpressed in both CF patients and model systems, is a regulator of CK2 kinase activity (48,49). Finally, our earlier studies demonstrated defective function of NDPK-A in CF cells (50), and NDPK is an in vivo CK2 target (51) that we have recently shown to not only regulate AMPK ␣1 but also to bind to CFTR (21,52). Thus, some of the reported targets of CK2 (27,53) include proteins controlling unexplained aspects of CF disease (50,54).…”
Section: Discussionmentioning
confidence: 98%
“…Immunoblotting-Immunoblotting was carried out as described previously (21). Briefly, blotted membranes were blocked for 30 min in TBS/Tween with 5% milk powder; and anti-NBD1 antibody (Neomarkers) was applied for 1.5 h followed by four 15-min washes, and then horseradish peroxidase-labeled anti-mouse secondary antibody was applied at a 1:5000 dilution for 45 min followed by four 15-min washes.…”
Section: Methodsmentioning
confidence: 99%
“…For example, NDPK-A activity is stringently regulated by 5= AMP-activated protein kinase (AMPK)-mediated phosphorylation, where AMPK␣1 interacts with NDPK-A via E124 to phosphorylate two adjacent residues, S122 and S144 (24)(25)(26). AMPK phosphorylates NDPK-A at S122 that augments its enzymatic activity by triggering substrate channeling.…”
mentioning
confidence: 99%